TRACER STUDY SYSTEM PORTAL-BASED SOCIAL NETWORK TO OPTIMIZE DATA COLLECTION ON HIGHER EDUCATION GRADUATES - Fitri Marisa; Dedi Usman Efendi; Indah Dwi Mumpuni (Proceeding International Conference on Information Technology and Business, 2016)
Background: Universities need to conduct data searches to graduate. This data can be used in a variety of needs. A media needed to connect between the faculty graduates or graduates with other graduates so that they can be interconnected. But it is constrained because most colleges difficulty in recruiting alumni data despite already done in various media. It is necessary for a more effective alternative media for support in collecting data of graduates. Method: The design of the portal using social network approach. So the first step is to design the parent website Tracer Study focus to accommodate the main data of graduates who are equipped with an interactive community features. Prototype portal tested and evaluated based on benchmarks dynamic, informative, and communicative, further refined to achieve an increase in visitors in every time data is consistent with the conditions or no distortion. Conclusion: The results of this research is a tracer study portal with social network approach to be one of the alternative media to attract graduates to interact with the media, and also that benefits the institution of data collection becomes more optimal.KEY WORDSPortal, Tracer Study, Social Network, Website, Alumni.